More substitutions changed team substitution strategy? An analysis of the FIFA World Cup 2002-2022 - Zheng Xiao; Hui Zhang (BMC, 2024)
Abstract Background The increase in the number of substitutions allowed in football from three to five has profoundly influenced the game. The impact of the rule change on the FIFA World Cup needs further verification. Methods A total of 2,151 team substitution opportunities and 2,410 substitutions in 384 matches from six FIFA World Cups (2002-2022) were analyzed to assess its impact. One-way ANOVA was used to assess differences in average substitution times among the six FIFA World Cups. Factors affecting the time of substitutions were explored using Generalized Linear Mixed Models. Results In each FIFA World Cup, over 92% of substitutions occurred during half-time and the second half, with a higher proportion in knockout stage matches than group stage matches. Group stage substitutions tended to happen earlier, particularly when teams were losing. As allowed substitutions increased, multiple substitutions in one opportunity rose from 4% to 38%. Of the 2,410 substitutions in the six FIFA World Cups, 21.45% were offensive, 63.65% were neutral and 14.90% were defensive. Winning teams made the highest percentage of defensive substitutions, while drawing or losing teams made the highest percentage of offensive substitutions. Match status significantly affected the time of the first three substitutions, and the presence of extra time significantly affected the time of the fourth substitution. Conclusion Analysis of substitutions in FIFA World Cups (2002-2022) reveals: Most substitutions occur during halftime and the second half; Substitutions are earlier in group stages, especially for losing teams; Increased allowed substitutions lead to more multiple-player substitutions; Defensive substitutions are more common when winning, while offensive ones are frequent when drawing or losing; Match status, ranking gap, extra time, game round, and substitution rules significantly influence the time of team substitutions.